Pengaruh Kualitas Pelayanan Publik Terhadap Kepuasan Masyarakat (Studi Kasus Di Desa Uelincu Kecamatan Pamona Utara Kabupaten Poso) - Novi Maryam Lempao; Join Hengkeng; Mikhael Jibrael Balo; Feliks Arfid Guampe* (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study aims to determine the effect of public service quality on community satisfaction in Uelincu Village, North Pamona District, Poso Regency. The research approach used is a quantitative approach. The study sample was 60 people from Uelincu village. The data obtained through the questionnaire was then processed using the help of SPSS 26 software. The data analysis technique used is simple regression analysis. The results showed that the quality of public services had a positive and significant effect on public satisfaction. Furthermore, the results of the coefficient of determination test showed that public satisfaction was able to be explained by the quality of public services by 45.7%. Thus, these results mean that the quality of good public services is one of the most important factors for the community. The better the public service by the village officials, the more the community's satisfaction with the government in the village will increase.